Rapid and Reliable Calibration of Laser Beam Deflection System for Microcantilever-Based Sensor Setups - HEGNER, MARTIN; MISHRA, ROHIT (My University, 2012)
Cantilever array-based sensor devices widely utilise the laser-based optical deflection method for measuring static cantilever deflections mostly with home-built devices with individual geometries. In contrast to scanning probe microscopes, cantilever array devices have no additional positioning device like a piezo stage. As the cantilevers are used in more and more sensitive measurements, it is important to have a simple, rapid, and reliable calibration relating the deflection of the cantilever to the change in position measured by the position-sensitive detector. We present here a simple method for calibrating such systems utilising commercially available AFM cantilevers and the equipartition theorem.
PUBLISHED
Keywords: Optics; Cantilever array-based sensors; Nanoscience & Materials